The Influence of Competence, Work Culture on the Performance of Elementary School Teachers in Gunungwungkal District - Hariyasasti, Yayuk (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This study aims to describe and analyze (1) The influence of competence on teacher performance in elementary schools in Gunungwungkal District, (2) The influence of work culture on teacher performance in elementary schools in Gunungwungkal District. The research method used is quantitative descriptive through a survey. Data collection was carried out through a questionnaire distributed to 67 elementary school teachers in Gunungwungkal District which was determined using the simple random sampling method, research data was obtained by distributing questionnaires online through social media. Data analysis used structural equality modeling (SEM). The results of the study showed that there was a positive and significant influence between competence on teacher performance and work culture had a significant effect on teacher performance.